Effects of preharvest ultraviolet‐C irradiation on fruit phytochemical profiles and antioxidant capacity in three strawberry (Fragaria × ananassa Duch.) cultivars. (21st January 2015) - Xie, Zhichun; Charles, Marie Thérèse; Fan, Jinshuan; Charlebois, Denis; Khanizadeh, Shahrokh; Rolland, Daniel; Roussel, Dominique; Deschênes, Martine; Dubé, Claudine
Abstract BACKGROUND Ultraviolet‐C (UV‐C) has proven effective in extending shelf‐life, reducing disease incidence and increasing the levels of health‐promoting compounds in several crops. While most studies were conducted at the postharvest stage, our study examined the effect of preharvest UV‐C application in three strawberry cultivars (Fragaria × ananassa Duch. 'Albion', 'Charlotte' and 'Seascape'). UV‐C treatment was applied from the onset of flowering until the fruits reached commercial maturity on plants grown for two consecutive seasons under greenhouse conditions. The phytochemical profiles and antioxidant capacity of the fruits were assessed at harvest. RESULTS The ellagic acid and kaempferol‐3‐glucuronide contents were significantly increased only in fruits of the cultivar 'Albion' collected from UV‐C‐treated plants in season 1. UV‐C did not consistently affect the other phenolic compounds that were measured. Based on the results of the ferric‐reducing antioxidant power, oxygen radical absorbance capacity and total phenolic content assays, the antioxidant capacity of the three strawberry cultivars was not affected by UV‐C. Season and cultivar had a decisive impact on these parameters. CONCLUSION The effect of preharvest UV‐C on the levels of bioactive compounds in strawberry fruits appears to be cultivar‐ dependent, with season or growing conditions having a significant impact. © 2014 Society of Chemical Industry